Effect of using educational media in familiarizing children with their rights in kindergartens in Sulaimaniyah (Raparin Journal of Humanities (RJH), 2023)
The aim of this study  was to determine the level of familiarity of kindergarten children with their rights ,as well as the effect of the use of educational media in familiarizing children with their rights ,and it is affected by variables such as (gender ,age, children' s ranking in the family).The researcher used an experimental approach, the research community was the (Kurd Genesis / 1 )  kindergarten in the western  education  directorate in the center of Sulaimaniyah   .The sample of study was (30) kindergarten children aged between (4,5) years, were purposely  selected , the tool used was individual interviews. The results of study showed that  the  level  familiarity  of kindergarten  children with their rights is low ,it was found that there was a statistically significant  difference between the pretest and the posttest ,and the difference was in favor of the posttest, indicating that the use of educational media had an effect on familiarizing children with their rights.It was also found that the variables (gender ,age ,children' s ranking in the family) had no affect on creating with children' s rights.